The legacy of Anthony Radivilovsky: state and prospects of research - V. V. Spivak (Ukrainian Cultural Studies, 2019)
The article is devoted to the review of the state and prospects of the study of the preaching heritage of Anthony Radivilovsky. The study first analyzed and systematized the experience gained by the national science in the field of research sermons Anthony Radivilovsky. These are the works of literary critics and linguists (S. Azovtseva, I. Isichenko, V. Krekotnya, M. Markovsky, O. Niki), historians (J. Frederic Berkoff, M. Gracia Bartolini, M. Kostomarov), philosophers (L. Dovgа). However, most of his sermons still remain beyond the attention of scholars. This is especially true of the handwritten legacy of Radivilovsky, which was only partially studied by literary scholars and almost not considered from a philosophical point of view. The most prominent methodological basis of the study was the methods of textual analysis, comparative studies and hermeneutic one. It is shown that for today domestic science has a considerable experience in studying the sermons of Anthony Radivilovsky. It is established that the data of the research, for the most part, are fragmentary in nature and relate to the literary qualities of the preacher’s work. The most significant proofs of Radivilovsky’s sermons remain in the works of M. Markovsky and V. Krekotnya. Instead, the philosophical component of his texts is poorly understood and requires detailed attention as the most promising direction in the study of Antony Radivilovsky’s texts. Potential directions of research of the philosophical component of Antony Radivilovsky’s heritage are: the study of philosophical traditions and texts on which the work of the preacher was based; consideration of the influence of philosophical knowledge and language on the content of the sermons of Radivilovsky; an analysis of the philosophical significance problems of his legacy concerning the range of semiotic issues, in particular, the moral and ethical nature.